Does the role and duties of the business rescue practitioner as conferred by the South African Companies Act 71 of 2008 give rise to conflicts with respect to the powers and duties of directors during business rescue proceedings? - Kaudeer, Ashirah Bibi (Department of Commercial Law, 2016)
The objective of this thesis is to research to what extent do the duties and powers conferred to the business rescue practitioner conflict with that of the directors during the business rescue proceedings since both of them form part of the management of the financially distressed company. In so doing, an analysis of the South African statutory provisions will be undertaken, followed by a probe into how those provisions can lead to the probable conflicts to be encountered between management and the practitioner, which can in turn considerably affect the effectiveness and success of the corporate reorganisation. In order to be able to find solutions to reduce possible conflicts, a juxtaposed analysis will be made with similarly statutory provisions in Australia, United Kingdom and United States of America.